Interspaces between word, gaze and touch: the Bible and the visual medium in the Middle Ages ; collected essays on Noli me tangere, the Woman with the Haemorrhage, the Head of John the Baptist - Baert, Barbara (Annua nuntia Lovaniensia, 2011)
"The basic focus which this book is concerned with, a strong new pact has been forged between Theology and Art History. Carefully calibrated methodologies have been developed to unite the world of the word and the world of the visual medium as a truly interdisciplinary research object. Historical-critical exegesis, church history, iconology and cultural anthropology together provide foundational support for knowledge of broader visual themes, and the functions of works of art. In their interplay they become the gateway to the "Interspaces of word, gaze and touch"--Back cover